Lignin / polylactic acid composite material as well as preparation method and application thereof
By preparing end-hydroxylated polylactic acid in the esterification reaction of polylactic acid and diol, and cross-linking reaction with isocyanate grafted lignin, it is solved that lignin and degradable polymers cannot be highly chemically connected in the prior art. The branch problem improves the mechanical properties and interface compatibility of the composite material.
Patent Information
- Application Number
- CN202310972180.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, lignin and degradable polymers cannot be highly chemically grafted, resulting in a low tensile strength of the prepared polymer composite.
By esterifying polylactic acid with diol, end-hydroxylated polylactic acid is prepared and cross-linked with isocyanate grafted lignin to form a lignin/polylactic acid composite material.
It improves the interface compatibility and mechanical properties of lignin/polylactic acid composite materials, and is suitable for packaging materials and plastic films.
Smart Images

Figure BDA0004375839580000081 
Figure BDA0004375839580000091 
Figure BDA0004375839580000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of degradable polymer composite materials, and specifically relates to a lignin / polylactic acid composite material and a preparation method and application thereof. Background Art
[0002] The exhaustion of fossil energy and the intensification of environmental crisis have made the development and utilization of biomass resources the current and future development direction. Lignin is a natural substance widely present in plant cell walls and a biomass resource with abundant reserves. Its storage in nature is second only to cellulose. However, the utilization rate of lignin is very low. Only 2% of lignin is commercially used in plastics and rubber. A large amount of lignin is discharged into rivers in the form of waste liquid or burned after concentration, resulting in waste of resources and serious pollution to the environment. As the only non-petroleum resource in nature that can provide renewable aromatic compounds, the rational and efficient application of lignin has positive significance for the environment and the economy. The simplest and most economical method is to directly use lignin or process it and directly fill polymer materials as a filler.
[0003] Polylactic acid, developed to solve the problem of traditional petroleum-based polymers being difficult to degrade, is the second largest synthetic biopolymer. The application range of polylactic acid includes food packaging, disposable household items, agricultural films, drug delivery systems, and implantable biomedical devices. Compared with thermoplastic polymers extracted and polymerized from non-renewable petroleum, polylactic acid can be made from agricultural renewable resources, such as wheat, corn starch, or straw, and in addition to biodegradability, the properties of polylactic acid are similar to those of polyethylene, polystyrene, or polypropylene, making polylactic acid produced at a lower cost more efficient. Therefore, blending such polymers with lignin is an effective method for modifying natural polymer materials. However, due to the poor dispersibility of lignin in the polylactic acid matrix, the interfacial adhesion between the two is poor, and it is difficult to prepare materials with excellent mechanical properties and processing properties by directly blending the two. Therefore, only by improving the interfacial compatibility between lignin and polylactic acid can the mechanical properties of the composite material be thoroughly improved to meet the needs of practical applications. For example, in the prior art, lactic acid and diols are polycondensed to prepare terminal hydroxylated polylactic acid to alleviate the above defects, but this method introduces a large amount of ethylene glycol structure into the polylactic acid molecule, thereby affecting the mechanical properties of the resulting material. Another example is Chinese patent document CN101486806A discloses a natural polymer / degradable polymer composite material and a preparation method thereof, wherein the degradable polymer is premixed with an active substance, and the natural polymer is premixed with a plasticizer, and then the two are blended in different proportions and extruded through a screw extruder to obtain a composite material. However, this method cannot ensure that the natural polymer and the degradable polymer are highly chemically grafted to form a network structure, and the tensile strength of the obtained polymer composite material is low (7.3-35.9MPa).
[0004] In actual application, due to the high cost of polylactic acid (PLA), the scope of use of PLA is limited. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defects in the prior art that lignin and degradable polymers cannot be highly chemically grafted and the tensile strength of the obtained polymer composite material is low, and a lignin / polylactic acid composite material and a preparation method and application are provided. The lignin / polylactic acid composite material has good interface compatibility, good mechanical properties and processing properties, etc.
[0006] The first object of the present invention is to provide an application of terminal hydroxylated polylactic acid in the preparation of lignin / polylactic acid composite materials, wherein the molecular weight of the terminal hydroxylated polylactic acid is 510-3600Da; and the terminal hydroxylation rate of the terminal hydroxylated polylactic acid is above 50%.
[0007] In the present invention, the molecular weight of the terminal hydroxylated polylactic acid is preferably 810-3050Da, more preferably 910-1650Da.
[0008] In the present invention, the terminal hydroxylation rate of the terminal hydroxylated polylactic acid is preferably 55%-99.9%. The terminal hydroxylation rate represents the conversion rate of the terminal hydroxyl groups in the polylactic acid.
[0009] In the present invention, the inventors found during the research and development process that when polylactic acid and diol are reacted, and the terminal hydroxylated polylactic acid is obtained by controlling the molecular weight of polylactic acid and the molar ratio of polylactic acid to diol, the terminal hydroxylation rate of the terminal hydroxylated polylactic acid can be made ≥50%.
[0010] In the present invention, the hydroxylated polylactic acid can be obtained by subjecting a mixed solution of polylactic acid and polyol to an esterification reaction.
[0011] Wherein, the molecular weight of the polylactic acid may be 500-3500Da, preferably 800-3000Da, and more preferably 900-1600Da. When the molecular weight of the polylactic acid is too large (e.g., 10000Da), the reaction activity is low, which may easily lead to incomplete end hydroxylation, affecting the subsequent cross-linking reaction with grafted lignin. When the molecular weight of the polylactic acid is too small, the obtained end hydroxylated polylactic acid may not be able to undergo cross-linking reaction with grafted lignin or the mechanical properties of the obtained lignin / polylactic acid composite material are poor.
[0012] The polyol may be an alcohol conventionally used in the art containing two or more hydroxyl groups (-OH) in the molecule, preferably a diol, such as ethylene glycol, 1,3-propylene glycol or 1,4-butanediol. The carbon number of the polyol is preferably 2-4.
[0013] Wherein, the molar ratio of the polylactic acid to the polyol may be 1:(0.5-2), preferably 1:(0.55-1.1).
[0014] The mixed solution of polylactic acid and polyol can be prepared by mixing the polylactic acid, the polyol and a solvent.
[0015] The solvent may be a conventional solvent in the art that can dissolve the polylactic acid and the polyol, such as dichloromethane, chloroform or acetonitrile.
[0016] Wherein, the esterification reaction is generally also added with a catalyst and a condensing agent. The type of the catalyst can be a conventional catalyst in the art, including 4-(dimethylamino)pyridine (DMAP), pyridine or triethylamine, such as (dimethylamino)pyridine (DMAP). The type of the condensing agent can be conventional in the art, including dicyclohexylcarbodiimide (DCC), N,N'-diisopropylcarbodiimide (DIC), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), O-benzotriazole-tetramethyluronium hexafluorophosphate (HBTU) or 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU), such as 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC).
[0017] The molar ratio of the polylactic acid to the condensation agent may be 1:(1-3), preferably 1:(1.1-2.0).
[0018] The molar ratio of the polylactic acid to the catalyst may be 1:(0.08-0.5), preferably 1:(0.08-0.2).
[0019] The temperature of the esterification reaction may be 20-35°C, preferably 20-30°C.
[0020] The time of the esterification reaction is not particularly limited, as long as the raw materials can be fully reacted, that is, extending the esterification reaction time does not increase the terminal hydroxylation rate of polylactic acid, for example, 18-30 hours.
[0021] After the esterification reaction is completed, filtering and drying steps are generally performed.
[0022] The filtration is generally performed using a poor solvent, which may be ether, methanol or ethanol, and the temperature may be -30°C to -15°C.
[0023] The drying conditions may be conventional in the art. The drying temperature may be 30-50° C., such as 40° C. The drying time may be 12-24 h, such as 12 h.
[0024] The second object of the present invention is to provide a lignin / polylactic acid composite material, which is obtained by cross-linking terminal hydroxylated polylactic acid and isocyanate grafted lignin;
[0025] Wherein, the molecular weight of the terminal hydroxylated polylactic acid is 510-3600Da; the terminal hydroxylation rate of the terminal hydroxylated polylactic acid is more than 50%;
[0026] Wherein, the mass ratio of the terminal hydroxylated polylactic acid to the isocyanate grafted lignin is (1-10):1.
[0027] In the present invention, the mass ratio of the terminal hydroxylated polylactic acid to the isocyanate grafted lignin is preferably (2.5-8):1, more preferably (3-6):1.
[0028] In the present invention, the molecular weight of the terminal hydroxylated polylactic acid is preferably 810-3050Da, more preferably 910-1650Da.
[0029] In the present invention, the terminal hydroxylation rate of the terminal hydroxylated polylactic acid is preferably 55%-99.9%.
[0030] In the present invention, the hydroxylated polylactic acid can be obtained by subjecting a mixed solution of polylactic acid and polyol to an esterification reaction.
[0031] Wherein, the molecular weight of the polylactic acid may be 500-3500Da, preferably 800-3000Da, and more preferably 900-1600Da. When the molecular weight of the polylactic acid is too large (e.g., 10000Da), the reaction activity is low, the end hydroxylation is incomplete, and the subsequent cross-linking reaction with the grafted lignin is affected. When the molecular weight of the polylactic acid is too small, the end hydroxylated polylactic acid obtained may not be able to undergo a cross-linking reaction with the grafted lignin or the mechanical properties of the obtained lignin / polylactic acid composite material are poor.
[0032] The polyol may be an alcohol having two or more hydroxyl groups (-OH) in the molecule conventionally used in the art, preferably a diol, such as ethylene glycol, 1,3-propylene glycol or 1,4-butanediol. The carbon number of the polyol is preferably 2-4.
[0033] Wherein, the molar ratio of the polylactic acid to the polyol may be 1:(0.5-2), preferably 1:(0.55-1.1).
[0034] The mixed solution of polylactic acid and polyol can be prepared by mixing the polylactic acid, the polyol and a solvent.
[0035] The solvent may be a conventional solvent in the art that can dissolve the polylactic acid and the polyol, such as dichloromethane, chloroform or acetonitrile.
[0036] Wherein, the esterification reaction is generally also added with a catalyst and a condensing agent. The type of the catalyst can be a conventional catalyst in the art, including 4-(dimethylamino)pyridine (DMAP), pyridine or triethylamine, such as (dimethylamino)pyridine (DMAP). The type of the condensing agent can be conventional in the art, including dicyclohexylcarbodiimide (DCC), N,N'-diisopropylcarbodiimide (DIC), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), O-benzotriazole-tetramethyluronium hexafluorophosphate (HBTU) or 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU), such as 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC).
[0037] The molar ratio of the polylactic acid to the condensation agent may be 1:(1-3), preferably 1:(1.1-2.0).
[0038] The molar ratio of the polylactic acid to the catalyst may be 1:(0.08-0.5), preferably 1:(0.08-0.2).
[0039] The temperature of the esterification reaction may be 20-35°C, for example 25°C.
[0040] The time of the esterification reaction is not particularly limited, as long as the raw materials can be fully reacted, that is, extending the esterification reaction time does not increase the terminal hydroxylation rate of polylactic acid, for example, 18-30 hours.
[0041] After the esterification reaction is completed, filtering and drying steps are generally performed.
[0042] A poor solvent is generally used during the filtration, and the poor solvent may be ether, methanol or ethanol at a temperature of -30°C to -15°C.
[0043] The drying conditions may be conventional in the art. The drying temperature may be 30-50° C., such as 40° C. The drying time may be 12-24 h, such as 12 h.
[0044] In the present invention, the grafting rate of the isocyanate-grafted lignin can be 30%-100%, preferably 34%-95%, preferably 65%-95%, and preferably 75%-91%.
[0045] In the present invention, the molecular weight of the isocyanate-grafted lignin may be 2000-7000 Da, preferably 2200-5500 Da, more preferably 4000-6500 Da.
[0046] In the present invention, the preparation method of the isocyanate-grafted lignin can be as follows: lignin and isocyanate are subjected to a grafting reaction in the presence of a solvent.
[0047] The type of lignin can be conventional in the art, such as alkali lignin, lignin sulfonate, organic solvent lignin or hot water hydrolyzed lignin, preferably alkali lignin or sulfonated lignin.
[0048] The molecular weight of the lignin may be 1000-2000 Da, preferably 1200-1500 Da.
[0049] The hydroxyl content of the lignin may be 1.5-3.8 mmol / g, preferably 2.0 mmol / g or 2.3 mmol / g. The hydroxyl content of the lignin may be determined by ion differential ultraviolet spectroscopy.
[0050] The type of the isocyanate can be conventional in the art, preferably a polyisocyanate, more preferably a diisocyanate, including 2,4-toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), norbornane diisocyanate (NBDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI) or xylylene diisocyanate (XDI), for example, hexamethylene diisocyanate (HDI) or 4,4'-diphenylmethane diisocyanate (MDI).
[0051] The mass ratio of the lignin to the isocyanate may be 1:(0.05-1.0), preferably 1:(0.1-0.6).
[0052] Before the lignin and the isocyanate are mixed with the solvent, preferably, a vacuum dehydration step is performed. The vacuum dehydration temperature may be 60-150° C. The vacuum dehydration time may be 1-5 hours.
[0053] The solvent may be a conventional solvent in the art that can dissolve the lignin and the isocyanate, preferably a polar solvent, including N,N-dimethylformamide and N,N-dimethylacetamide.
[0054] A catalyst is generally added to the grafting reaction. The type of the catalyst can be conventional in the art, preferably a metal catalyst and / or an amine catalyst. The metal catalyst preferably includes one or more of stannous octoate, stannous benzoate, dibutyltin dilaurate, tetraisobutyl titanate, lead octoate, iron octoate and cobalt octoate, such as stannous octoate. The amine catalyst preferably includes a tertiary amine catalyst, such as one or more of triethylamine, triethylenediamine and tetramethylbutylene diamine.
[0055] The mass ratio of the lignin to the catalyst may be 1:(0.002-0.01), for example, 1:0.0025, 1:0.003 or 1:0.005.
[0056] The atmosphere of the grafting reaction is preferably nitrogen or an inert atmosphere.
[0057] The temperature of the grafting reaction may be 50-120°C, preferably 50-100°C, and more preferably 55-85°C.
[0058] The grafting reaction time may be 3-16 hours, preferably 5-10 hours, and more preferably 6-10 hours.
[0059] The grafting reaction is generally stirred during the process.
[0060] In the present invention, the tensile strength of the lignin / polylactic acid composite material may be 45-70 MPa, preferably 45-65 MPa, preferably 50-65 MPa, and preferably 55-65 MPa.
[0061] In the present invention, the elongation at break of the lignin / polylactic acid composite material may be 15%-40%, more preferably 25%-40%.
[0062] In the present invention, the impact strength of the lignin / polylactic acid composite material can be 10-20 KJ·m -2 .
[0063] The third object of the present invention is to provide a method for preparing the lignin / polylactic acid composite material as described above, which comprises the following steps: subjecting the terminal hydroxylated polylactic acid and the isocyanate grafted lignin solution to a cross-linking reaction;
[0064] Wherein, the molecular weight of the terminal hydroxylated polylactic acid is 510-3600Da; the terminal hydroxylation rate of the terminal hydroxylated polylactic acid is more than 50%;
[0065] Wherein, the mass ratio of the terminal hydroxylated polylactic acid to the isocyanate grafted lignin is (1-10):1.
[0066] In the present invention, the mass ratio of the terminal hydroxylated polylactic acid to the isocyanate grafted lignin is preferably (2.5-8):1, more preferably (3-6):1.
[0067] In the present invention, the cross-linking reaction refers to a process in which molecules are cross-linked in a polymer material by forming chemical bonds or physical effects to form a three-dimensional network structure.
[0068] In the present invention, the cross-linking reaction is preferably carried out under nitrogen or an inert atmosphere.
[0069] In the present invention, the temperature of the cross-linking reaction may be 30-95°C, preferably 60-90°C, more preferably 75-85°C.
[0070] In the present invention, the cross-linking reaction time may be 4-10 hours, preferably 4-8 hours.
[0071] In the present invention, the cross-linking reaction is generally followed by filtering and drying steps.
[0072] The filtration is preferably performed by adding a poor solvent. The type of the poor solvent can be conventional in the art, such as ethanol.
[0073] The fourth object of the present invention is to provide a use of the lignin / polylactic acid composite material as described above as an agricultural mulch film or packaging material.
[0074] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0075] The reagents and raw materials used in the present invention are commercially available.
[0076] The positive and progressive effect of the present invention is that a lignin / polylactic acid composite material can be obtained by controlling the molecular weight and the hydroxylation rate of the terminal hydroxylated polylactic acid and performing a cross-linking reaction with isocyanate-grafted lignin. The material not only improves the processability of lignin, which has a great guiding significance for the industrial application of lignin, but also maintains the biodegradability of polylactic acid. The composite material has good interface compatibility, excellent mechanical properties, processing properties and degradation properties, and is suitable for packaging materials, ground films and other fields. DETAILED DESCRIPTION
[0077] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0078] The raw materials of the following examples and comparative examples are all commercially available.
[0079] The CAS number of polylactic acid is 26100-51-6; the CAS number of the condensation agent EDC is 1892-57-5; and the CAS number of the catalyst DMAP is 1122-58-3.
[0080] Lignin (alkali lignin and sulfonated lignin) was provided by Shanghai Cathay Biotechnology Co., Ltd.
[0081] Examples 1-15, Comparative Example 1
[0082] The formulas for preparing terminal hydroxylated polylactic acid in Examples 1-15 and Comparative Example 1 are shown in Table 1 below:
[0083] Table 1
[0084]
[0085]
[0086] The preparation method of terminal hydroxylated polylactic acid of Examples 1-15 and Comparative Example 1 comprises the following steps: mixing polylactic acid, ethylene glycol, a solvent, a catalyst and a condensation agent, reacting at 25°C for 24 hours, filtering, mixing the filtrate with a poor solvent at -15°C, and drying at 40°C for 12 hours.
[0087] The formulas for preparing isocyanate-grafted lignin and lignin / polylactic acid composite materials according to Examples 1-15 and Comparative Example 1 are shown in Table 2:
[0088] Table 2
[0089]
[0090]
[0091] The preparation method of the lignin / polylactic acid composite material of Examples 1-15 and Comparative Example 1 comprises the following steps:
[0092] (1) Preparation of isocyanate-grafted lignin: Lignin and isocyanate were vacuum dehydrated at 100°C for 2 h, a solvent and a catalyst were added, and the mixture was stirred to make it uniform. The mixture was stirred and reacted at 70°C for 6 h under a nitrogen atmosphere to obtain an isocyanate-grafted lignin solution.
[0093] (2) Preparation of lignin / polylactic acid composite material: Add end-hydroxylated polylactic acid to the isocyanate-grafted lignin solution, react at 80°C for 8 h under a nitrogen atmosphere, then pour the solution into 500 mL of ethanol, filter, and dry the filter cake.
[0094] Comparative Example 2
[0095] The difference from Example 1 is that in the preparation method of the lignin / polylactic acid composite material of Comparative Example 2, the polylactic acid is not terminally hydroxylated, the molecular weight of the polylactic acid is 2000 Da, and the mass ratio of the polylactic acid to the grafted lignin is 80:20.
[0096] The preparation method is as follows:
[0097] (1) Preparation of isocyanate-grafted lignin: Lignin and isocyanate were vacuum dehydrated at 100°C for 2 h, a solvent and a catalyst were added, and the mixture was stirred to make it uniform. The mixture was stirred and reacted at 70°C for 6 h under a nitrogen atmosphere to obtain an isocyanate-grafted lignin solution.
[0098] (2) Preparation of lignin / polylactic acid composite material: Polylactic acid was added to the isocyanate grafted lignin solution, reacted at 80°C for 8 h under nitrogen, and then the solution was poured into 500 mL of ethanol, filtered, and the filter cake was dried.
[0099] Effect Example 1
[0100] The terminal hydroxylation rate and the molecular weight of the terminal hydroxylated polylactic acid prepared in Examples 1-15 and Comparative Examples 1-2 were measured.
[0101] The method for determining the terminal hydroxylation rate is as follows: the terminal carboxyl content of the polylactic acid before and after the terminal hydroxylation reaction is measured by potentiometric titration, thereby obtaining the terminal hydroxylation rate.
[0102] The molecular weight of the hydroxylated polylactic acid was determined by matrix-assisted laser desorption time-of-flight mass spectrometry (MALDI-TOF).
[0103] The measurement results are shown in Table 3.
[0104] Table 3
[0105]
[0106]
[0107] Effect Example 2
[0108] The grafting rate and molecular weight of the isocyanate grafted lignin prepared in Examples 1-15 and Comparative Examples 1-2 were measured.
[0109] The method for determining the grafting rate is: nuclear magnetic resonance method.
[0110] The molecular weight of isocyanate grafted lignin was determined by matrix-assisted laser desorption time-of-flight mass spectrometry (MALDI-TOF).
[0111] The measurement results are shown in Table 4.
[0112] Table 4
[0113]
[0114]
[0115] Effect Example 3
[0116] The lignin / polylactic acid composite materials prepared in Examples 1-15 and Comparative Examples 1-2 were mixed and dissolved with N,N'-dimethylformamide to form a solution with a concentration of 1 g / mL, cast on a glass culture dish, dried at 12°C for 10 hours, and then vacuum dried at 60°C for 8 hours to obtain a film-like lignin / polylactic acid composite material. The mechanical properties were tested, the test standards are shown in Table 5, and the test results are shown in Table 6.
[0117] Table 5
[0118] Performance Indicators Test Standards Tensile strength / MPa GB / T 1040.2-2006 Elongation at break / % GB / T 1040.2-2006 <![CDATA[Impact strength / KJ·m -2 > GB / T 1843-2008
[0119] Table 6
[0120]
[0121]
[0122] It can be seen from Table 6 that, as described in Examples 1-15, the end-hydroxylated polylactic acid prepared from polylactic acid with a moderate molecular weight and then grafted with isocyanate to obtain a lignin / polylactic acid composite material has good mechanical properties.
[0123] In Comparative Example 1, polylactic acid with a molecular weight of 10,000 Da was used. Since its reaction activity was greatly reduced, the end hydroxylation rate of polylactic acid was low, and thus the degree of crosslinking with the grafted lignin was low, resulting in reduced overall mechanical properties of the lignin / polylactic acid composite material.
[0124] In Comparative Example 2, the overall mechanical properties of the lignin / polylactic acid composite material prepared by using polylactic acid that has not been terminally hydroxylated are relatively poor.
Claims
1. Application of terminal hydroxylated polylactic acid in the preparation of lignin / polylactic acid composite materials, characterized in that: The molecular weight of the terminal hydroxylated polylactic acid is 510-3600Da; the terminal hydroxylation rate of the terminal hydroxylated polylactic acid is above 50%.
2. The use of the hydroxylated polylactic acid according to claim 1 in the preparation of a lignin / polylactic acid composite material, characterized in that: The molecular weight of the terminal hydroxylated polylactic acid is 810-3050Da; And / or, the terminal hydroxylation rate of the terminal hydroxylated polylactic acid is 55%-99.9%.
3. The use of the hydroxylated polylactic acid according to claim 1 in the preparation of a lignin / polylactic acid composite material, characterized in that: The terminal hydroxylated polylactic acid is obtained by subjecting a mixed solution of polylactic acid and polyol to an esterification reaction; The molecular weight of the polylactic acid is preferably 500-3500Da, more preferably 800-3000Da, and more preferably 900-1600Da; The molar ratio of the polylactic acid to the polyol is preferably 1:(0.5-2), more preferably 1:(0.55-1.1).
4. A lignin / polylactic acid composite material, characterized in that: The end-hydroxylated polylactic acid and isocyanate-grafted lignin are cross-linked to obtain the obtained product; Wherein, the molecular weight of the terminal hydroxylated polylactic acid is 510-3600Da; the content of terminal hydroxyl groups in the terminal hydroxylated polylactic acid is more than 50%; Wherein, the mass ratio of the terminal hydroxylated polylactic acid to the isocyanate grafted lignin is (1-10):
1.
5. The lignin / polylactic acid composite material according to claim 4, characterized in that: The molecular weight of the terminal hydroxylated polylactic acid is 810-3050Da, preferably 910-1650Da; And / or, the terminal hydroxylation rate of the terminal hydroxylated polylactic acid is 55%-99.9%; And / or, the mass ratio of the terminal hydroxylated polylactic acid to the isocyanate grafted lignin is (2.5-8):1, preferably (3-6):1; And / or, the grafting rate of the isocyanate-grafted lignin is 30%-100%, preferably 34%-95%, preferably 65%-95%, preferably 75%-91%; And / or, the molecular weight of the isocyanate grafted lignin is 2000-7000Da, preferably 2200-5500Da, preferably 4000-6500Da.
6. The lignin / polylactic acid composite material according to claim 4, characterized in that: The terminal hydroxylated polylactic acid is obtained by subjecting a mixed solution of polylactic acid and polyol to an esterification reaction; The molecular weight of the polylactic acid is preferably 500-3500Da, more preferably 800-3000Da, and more preferably 900-1600Da; The molar ratio of the polylactic acid to the polyol is preferably 1:(0.5-2), more preferably 1:(0.55-1.1); And / or, the preparation method of the isocyanate grafted lignin is: lignin and isocyanate are subjected to a grafting reaction in the presence of a solvent; The molecular weight of the lignin is preferably 1000-2000Da, more preferably 1200-1500Da; The hydroxyl content of the lignin is preferably 1.5-3.8 mmol / g; The mass ratio of the lignin to the isocyanate is preferably 1:(0.05-1.0), more preferably 1:(0.1-0.6).
7. The lignin / polylactic acid composite material according to claim 4, characterized in that: The tensile strength of the lignin / polylactic acid composite material is 40-70MPa, preferably 45-65MPa, preferably 50-65MPa, preferably 55-65MPa; And / or, the elongation at break of the lignin / polylactic acid composite material is 15%-40%, preferably 25%-40%; And / or, the impact strength of the lignin / polylactic acid composite material is 10-20 KJ·m -2 .
8. A method for preparing a lignin / polylactic acid composite material according to any one of claims 4 to 7, characterized in that: The method comprises the following steps: subjecting the terminal hydroxylated polylactic acid and the isocyanate grafted lignin solution to a cross-linking reaction; Wherein, the molecular weight of the terminal hydroxylated polylactic acid is 510-3600Da; the terminal hydroxylation rate of the terminal hydroxylated polylactic acid is more than 50%; Wherein, the mass ratio of the terminal hydroxylated polylactic acid to the isocyanate grafted lignin is (1-10):
1.
9. The method for preparing the lignin / polylactic acid composite material according to claim 8, characterized in that: The temperature of the cross-linking reaction is 30-95°C, preferably 60-90°C, more preferably 75-85°C; And / or, the cross-linking reaction time is 4-10 hours, preferably 4-8 hours; And / or, filtering and drying steps are further performed after the cross-linking reaction; And / or, the mass ratio of the terminal hydroxylated polylactic acid to the isocyanate grafted lignin is (2.5-8):1, preferably (3-6):
1.
10. Use of the lignin / polylactic acid composite material as claimed in any one of claims 4 to 7 as agricultural mulch film or packaging material.
Citation Information
Patent Citations
Natural polymer / degradable polymer composite material and preparation thereof
CN101486806A